Cross‐Sectional Imaging Modalities in Correlation to the Thrombolysis in Cerebral Infarction Score: The Next Frontier in Adjunctive Endovascular Stroke Therapy - Johannes Kaesmacher; Kilian M. Treurniet; Manon Kappelhof; Tomas Dobrocky; Johanna Ospel; Adnan Mujanovic; Jens Fiehler; Bernard Yan; Mayank Goyal; Albert J. Yoo; Bruce Campbell; Osama O. Zaidat; et al. (Stroke: Vascular and Interventional Neurology)
The expanded Thrombolysis in Cerebral Infarction (eTICI) scale is the default method to measure reperfusion success of endovascular treatment for acute ischemic stroke. It is an estimate of the percentage of the vascular territory affected by the initial occlusion, or target downstream territory (TDT), that is reperfused after the intervention. Traditionally, the size of the TDT is determined on the preinterventional catheter angiography images by delineating the antegrade capillary deficit caused by the catheter angiography target occlusion. As such, the current definition of eTICI grading is only suitable to estimate the efficacy of reperfusion strategies occurring after the baseline catheter angiogram. However, reperfusion therapy for acute ischemic stroke due to large vessel occlusion often encompasses intravenous thrombolysis therapy started prior to endovascular treatment but after cross‐sectional vascular imaging (computed tomography or magnetic resonance imaging) used to determine eligibility for endovascular treatment. The inherent shortcomings of the current eTICI scale to quantify preinterventional perfusion changes are discussed. We then argue that depending on the timing of the studied intervention – either between cross‐sectional imaging and endovascular treatment or after first intracranial catheter angiography – the TDT used to determine the eTICI grade should be based on the occlusion as seen on admission cross‐sectional vascular imaging or prethrombectomy catheter angiography, respectively. We propose a new conceptual framework to grade reperfusion based on the TDT derived from the occlusion seen on cross‐sectional vascular imaging: the cross‐sectional eTICI. Last, we discuss how this definition of the TDT more reliably measures preinterventional reperfusion and establishes homogenous definitions of embolization and infarctions in new territories.